Microbiota and cancer (review of literature) - M. F. Vecherkovskaya; G. V. Tetz; V. V. Tetz (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Article presents current data on the contribution of the human microbiota to the development of oncological conditions, microbial impact on cell transformation, influence on chemotherapy outcome. Brief description of the methods used for studying microbiota in carcinogenesis as well as prospects of creating non-invasive diagnostic tools is given.